2017
DOI: 10.1021/acs.analchem.7b01747
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled DNA Generated Electric Current Biosensor for HER2 Analysis

Abstract: We have developed a new DNA self-assembly amplification technology that generates electric current for electrochemical biosensing. The new technology was used for detection of human epidermal growth factor receptor 2 (HER2). In our technology, an aptamer was utilized both as a ligand for recognition and as a signal generating reporter. The aptasensor is based on a sandwich format and a DNA primer on a HER2 aptamer initiates auxiliary DNA self-assembled on the electrode to form a long one-dimensional DNA. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…In this study, a sandwich-type aptamer and a DNA primer could form a long one-dimensional DNA which was treated with molybdate for generation of electrochemical current. According to the obtained results, the prepared aptasensor for HER2 detection in serum was highly correlated with ELISA measurements [21]. Finally, an aptamer-based colorimetric technique based on AuNPs was developed for HER2 detection.…”
Section: Introductionmentioning
confidence: 75%
“…In this study, a sandwich-type aptamer and a DNA primer could form a long one-dimensional DNA which was treated with molybdate for generation of electrochemical current. According to the obtained results, the prepared aptasensor for HER2 detection in serum was highly correlated with ELISA measurements [21]. Finally, an aptamer-based colorimetric technique based on AuNPs was developed for HER2 detection.…”
Section: Introductionmentioning
confidence: 75%
“…Currently, many novel strategies about signal amplification based on functional nanomaterials , enzyme‐signal , DNA self‐assembly and so on have been established for improving sensitivity of electrochemical detection. Among of them, a common method is to introduce a homogeneous chemical reaction coupled with electrode reaction for signal amplification.…”
Section: Introductionmentioning
confidence: 99%
“…Combined testing of both EGFR mutation and HER2 protein expression level in peripheral blood may better predict the efficacy of EGFR-TKI on advanced NSCLC. Research data showed that the concentration of HER2 in breast cancer patient's blood elevate to 15-75 ng/mL compared to 2-15 ng/mL in normal individuals 23 . The amount of HER2 in the blood of healthy people is 2-15 ng/mL, which can explain the high expression of HER2 in cancer patients.…”
Section: Discussionmentioning
confidence: 99%